Turbo Pascal - Mojena, Richard (Wadsworth Pub. Co., 1992)
Using the power of Turbo Pascal 6.0 - the latest Turbo release - this book is based on three guiding principles: top-down design from the start, cohesive treatment of topics, and flexibility of coverage. Core design and development topics are introduced early and expanded throughout.